The G Protein–Coupled Receptor GPR30 Mediates the Nontranscriptional Effect of Estrogen on the Activation of PI3K/Akt Pathway in Endometrial Cancer Cells. Issue 1 (1st January 2013) - Ge, Xin; Guo, Ruixia; Qiao, Yuhuan; Zhang, Yancai; Lei, Jia; Wang, Xinyan; Li, Liuxia; Hu, Dongmei
Abstract : Objective: The goal of this study was to investigate the effect of G protein–coupled receptor 30 (GPR30) on the activation of PI3K/Akt pathway induced by E2 in endometrial cancer cells. Methods and materials: Immunohistochemistry was performed to determine the location and expression of GPR30, estrogen receptors (ERs), Akt, and phosphorylated Akt. We also investigated the expression of GPR30, ERs, and the level of phosphorylation of Akt induced by E2 in endometrial cancer cells, Ishikawa cells, and HEC-1A cells. We down-regulated the expression of GPR30 in endometrial cancer cell lines by transfection with shGPR30-pGFP-V-RS, a GPR30 antisense expression vector. The cells were then subjected to a proliferation assay. Immunoprecipitation assay was performed to determine whether GPR30 directly bind to PI3K. The stable transfected cells resuspension of 100 μL (5 × 10 6 cells) was injected subcutaneously into the right flank of athymic mice to perform xenograft tumor formation assays. Results: E2 stimulated cell proliferation and induced GPR30 expression and PI3K/Akt pathway activation in endometrial cancer cells, Ishikawa cells, and HEC-1A cells, whereas the expression of ERs remained unchangeable. Down-regulation of GPR30 decreased the phosphorylation of Akt and reduced cell proliferation, and GPR30 did not bind to PI3K. Down-regulation of GPR30 significantly inhibited the tumor growth of HEC-1A cells in athymic nude mice. Conclusions: These findings suggest that GPR30 mediates the nontranscriptional effect of estrogen on the activation of PI3K/Akt pathway in endometrial cancer cells.